Pre-election violence and territorial control: Political dominance and subnational election violence in polarized African electoral systems. (January 2020) - Wahman, Michael; Goldring, Edward
Cross-national research on African electoral politics has argued that competition increases the prospects for pre-election violence. However, there is a dearth of systematic research on the effect of political competition on pre-election violence at the subnational level. We theorize that in African democracies characterized by competition at the national level but low subnational competitiveness (polarization), violence is often a manifestation of turf war and a tool to maintain and disrupt political territorial control. Consequently, contrary to expectations derived from the cross-national literature, pre-election violence is more likely in uncompetitive than competitive constituencies. Locally dominant as well as locally weak parties have incentives to perpetrate violence in uncompetitive constituencies. For locally dominant parties, violence is a tool to shrink the democratic space in their strongholds and maintain territorial control. For locally weak parties, violence can disturb the dominance of the opponent and protect their presence in hostile territory. We hypothesize that pre-election violence will be particularly common in opposition strongholds. In such locations, ruling parties can leverage their superior repressive resources to defend their ability to campaign, while the opposition can use their local capacity to reinforce the politics of territoriality. We test our hypotheses with original constituency-level election violence data from the 2016 Zambian elections. Data come from expert surveys of domestic election observers and represent a novel way of measuring low-level variations in election violence. Our analysis shows patterns of pre-election violence consistent with our theory on pre-election violence as a territorial tool.